Healthy behavior and herbal drink consumption among educated youth during COVID-19 pandemic - Priyono Tri Febrianto; Arum Budiastuti; Lutfi Apreliana Megasari; Merlia Indah Prastiwi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2023)
The coronavirus (COVID-19) pandemic has affected social and economic sectors and has created new behavior and lifestyles. This article employs a quantitative methodological approach. Through interviews with 274 university students in East Java, Indonesia, the findings suggest that young people’s awareness of health behavior shifted after the spread of COVID-19. Before the pandemic, parents are struggling to have their children consume herbs. Youngsters consider herbs as a traditional lifestyle for the elderly. However, after COVID-19, the results suggest that young people are more supportive of herbal medicine in order to protect themselves from COVID-19. Therefore, it can be argued that COVID-19 pandemic generates a growing awareness for young people to consume herbal medicine, which becomes a new lifestyle and preserves the nation’s centuries-worth wisdom of the local culture.